INTERSECTIONALITY OF HUMAN RIGHTS, BUSINESS AND DISABILITIES - Ahmed, Ahmed Rufai (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
As businesses face increasing expectations to uphold human rights, disability remains a largely marginalized concern within corporate agendas. This paper investigates the intersection of human rights, business practices, and disability, arguing that an inclusive approach not only fulfils ethical and legal obligations but also unlocks innovation and long-term value creation. Drawing on analyses of international frameworks most notably the UN Convention on the Rights of Persons with Disabilities and a series of global corporate case studies, the paper demonstrates how embedding disability into human rights due diligence enables companies to identify and remediate discrimination, design universally accessible products, and cultivate inclusive work environments. An intersectional lens further reveals how gender, race, and socioeconomic status can intensify barriers for people with disabilities, highlighting the need for differentiated policy responses. The study concludes by proposing a multi-stakeholder roadmap encompassing policy reform, cross-sector partnerships, and sustained stakeholder engagement to integrate disability rights into corporate governance and foster truly inclusive business ecosystems.